Nilai-Nilai Islam Pada Tahapan Mappacci Di Kecamatan Patampanua Kabupaten Pinrang - Fatmawati Fatmawati; Abd. Rahim Arsyad; Muhammad Qadaruddin (Jurnal Kajian Manajemen Dakwah, 2021)
This study discusses the Islamic values ​​contained in the mappacci stage. This research is intended to answer the problem: how is the procession of implementing the mappacci tradition? What are the Islamic values ​​contained in the mappacc stages? How does POAC function in the implementation of the imappacci tradition? This study uses a sociological approach to communication. The research data sources are primary data sources and secondary data sources. Furthermore, the data collection method was carried out through four stages, namely: data reduction, data presentation, and drawing conclusions. Data collection techniques used are observation, interviews, and documentation. Based on the results of the research, the preparation and procession in the mappacci ceremony is a Bugis Patampanua tradition whose implementation uses pacci leaves which are a form of hope and prayer for the welfare and happiness of the prospective bride and groom, which are arranged in a summary of nine types of equipment. Pillows, silk covers, jackfruit leaves, banana shoots, pacci leaves, rice, candles, pacci holders, brown sugar and coconut. Thus the meaning contained in the equipment in the mappacci ceremony which is always carried out at every wedding of the Bugis Patampanua community. The implementation of the mappacci ceremony contains a symbolic meaning of cleanliness or holiness which aims to cleanse the soul and body of the prospective bride and groom before navigating the household ark. Based on the conclusions from the results of the research, the researchers suggest: The Bugis Patampanua community still maintains the culture that has been inherited from their ancestral culture and it is hoped that the younger generation can preserve the culture, where the culture of the traditional mappacci wedding ceremony of Bugis Patampanua contains values ​​and meanings of life messages that aim to good. Enriching the repertoire of local culture, with the demands of Islamic teachings so that there are no elements of polytheism and things that deviate from the true teachings of Islam, thanks to the arrival of Islam has given a new color to the Bugis tribe in Patampanua District, Pinrang Regency, especially the mappacci procession